Toll-like receptor 4-mediated inflammatory stimulation in Kupffer cell enhances arsenite-induced liver fibrosis by triggering hepatic stellate cell activation - Qian Song; Meitong Zhou; Rui He; Heng Diao; Lili Fan; Chenglong Tu; Xiong Chen; Dapeng Wang (Ecotoxicology and Environmental Safety)
As a metalloid element with toxic properties, arsenic (As) has been shown to induce liver fibrosis (LF). Activation of hepatic stellate cell (HSC) is a pivotal factors in the progression of LF, yet the key sentinel cells of the liver tissue, Kupffer cell (KC), also exert a central regulatory role in driving LF. However, the specific functions of these cells in As-induced LF remain to be elucidated. Toll-like receptor 4 (TLR4) triggering the release of inflammatory cytokines via activating downstream nuclear transcription factor-κB (NF-κB) signaling pathways. This study employed primary rat KC (PRKC) and constructed a co-culture cell model of PRKC with HSC to investigate the effect of TLR4-mediated inflammatory response of KC on the activation of HSC under As exposure. The results demonstrated that As exposure can activate the TLR4 signaling pathway in PRKC, as evidenced by increased secretion of TLR4-mediated pro-inflammatory factors. Notably, the activation of the TLR4 signaling pathway in PRKC induced by As is responsible for HSC activation, which was confirmed through interventions with lipopolysaccharide (LPS, a TLR4 agonist) and TAK-242 (a TLR4 inhibitor). This study emphasizes the TLR4-mediated inflammatory response in KC may serve as a critical mechanism underlying As-induced LF.